Strengthening of Reinforced Concrete Beam Elements by Wrapping with Gfrp - Tamil Selvi, Dr; P.B. Sakthivel, Dr; PoornimaGandhi, R (International Journal of Engineering and Technology, 2018)
Structural elements need to strengthening and retrofitting works as a result of ageing, upgrading of structure due to new design codes or any Environmental issues. The strengthening or retrofitting of existing structures are done externally to the structural members using various techniques such as jacketing, retrofitting, guniting and shotcreting, and ferrocement techniques. The experiment is carried out to increase the load carrying capacity of structure by wrapping externally the beam elements with Glass Fibre Reinforced Polymer mats (GFRP) is wrapped around the beam elements. The load carrying capacity is analysed using single and double layer wraps on damaged and undamaged specimens and compare with conventional beam as control specimens. Beam specimens of size 750 mm x 150 mm x 150 mm with M30 Grade concrete used in the experiment. The result of flexural strength and load – deflection of test and control beam have brought out with energy absorption coefficient. The study results have demonstrated that the performance of 1 layer GFRP wrapped beams show an increased load carrying capacity of 1.86 times of that of conventional beam, and 2 layer  GFRP wrapped beam show an increase  in load capacity of 2.6 times of that of conventional concrete.